A systematic literature review: The phenomenon of academic burnout among generation Alpha amid the hectic dynamics of modern learning - Rohmaniyah, Alfiatur; Atiyah, Atiyah; Ani, Ani (Priviet Social Sciences Journal, 2025)
Academic burnout is becoming increasingly visible among Generation Alpha, who are growing up in fast-paced, highly structured, and competitive digital learning environments. High-performance expectations, continuous exposure to technology, and limited social-emotional support have been shown to reduce students’ psychological well-being and intrinsic learning motivation. This study aimed to identify the main factors contributing to academic burnout among Generation Alpha and formulate preventive strategies that align with the current educational landscape. This study employed a Systematic Literature Review (SLR) by adapting the PRISMA guidelines. Data were collected from reputable international and national journals indexed in Scopus, ScienceDirect, Google Scholar, and Garuda, published between 2019 and 2025. Of the 65 articles initially identified, 30 met the inclusion criteria and were analyzed thematically using Braun and Clarke’s approach. The results show that academic performance pressure is the most dominant factor contributing to burnout (reported in 60% of studies). Digital fatigue caused by multitasking appears in 53% of the findings, while limited social-emotional support from families and teachers is highlighted in 47% of the studies. Effective preventive strategies include the implementation of Social Emotional Learning (SEL), reinforcement of self-regulated learning skills, and strong collaboration between schools and parents to create a balanced and empathetic learning climate. These findings emphasize the importance of a holistic educational paradigm that equally prioritizes academic achievement and emotional well-being, enabling Generation Alpha to develop resilience and adaptability in navigating modern learning challenges in the future.